2013
DOI: 10.1177/1060028013509232
|View full text |Cite|
|
Sign up to set email alerts
|

Dimethyl Fumarate (Tecfidera)

Abstract: In March 2013, dimethyl fumarate was approved as a third oral option for patients with relapsing forms of MS. Although no head-to-head trials have been conducted, a comparison of data from phase III trials suggests that the efficacy of dimethyl fumarate is comparable to that of existing oral agents and may offer a preferable safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…To do this, we utilized the fumaric acid ester monomethyl fumarate (MMF). MMF is the active metabolite of dimethyl fumarate, which is now approved for treatment of multiple sclerosis (69, 70). Importantly, we have previously shown that MMF successfully ameliorates ROS accumulation and antiretroviral-induced toxicity in neuroglial cell cultures (32).…”
Section: Resultsmentioning
confidence: 99%
“…To do this, we utilized the fumaric acid ester monomethyl fumarate (MMF). MMF is the active metabolite of dimethyl fumarate, which is now approved for treatment of multiple sclerosis (69, 70). Importantly, we have previously shown that MMF successfully ameliorates ROS accumulation and antiretroviral-induced toxicity in neuroglial cell cultures (32).…”
Section: Resultsmentioning
confidence: 99%
“…In 2013 dimethyl fumarate (Tecfidera) was approved by the FDA as a first-line therapy for adults with relapsing MS, although its mechanism of action remains largely unknown [55] . α-NETA and dimethyl fumarate share certain features such as small size (242 Da and 144 Da, respectively) and simplicity in structure.…”
Section: Discussionmentioning
confidence: 99%
“…Currently DMF is approved by the FDA to treat patients with relapsing multiple sclerosis (MS). Other NRF2 activators are also being investigated in clinical trials for a variety of diseases [107, 108]. Sulforaphane (SFN) is an isothiocyanate that is naturally present in cruciferous vegetables such as broccoli and cabbage.…”
Section: Modulation Of Nrf2 Signaling: Nrf2 Activatorsmentioning
confidence: 99%